Gujarati in Singapore - Shah, Sheena (Routledge, 2020)
Singapore has four official languages: Malay, Mandarin, Tamil, and English. In its bilingual education policy, English is studied as a first language and an officially assigned ethnic mother tongue language (MTL) as a second language. Since 1990, five South Asian languages, which are considered ‘semi-official’ MTLs, can be chosen. These languages – Bengali, Gujarati, Hindi, Punjabi, and Urdu – are commonly referred to as non-Tamil Indian languages. Among them, Gujarati is the language with the lowest and consistently declining student enrolment. Three main factors can explain this: 1) weekend classes and inappropriate teaching materials deter students from attending Gujarati classes, 2) the lack of interest among the local as well as immigrant younger generation, and 3) sentimental reasons of choosing Gujarati are outweighed by pragmatic considerations that lead to the choice of more widely spoken languages as MTLs. Gujarati loses out to both the socioeconomically advantageous Mandarin and the national Indian language Hindi.